2021
DOI: 10.3390/v13091810
|View full text |Cite
|
Sign up to set email alerts
|

Gypenoside Inhibits Bovine Viral Diarrhea Virus Replication by Interfering with Viral Attachment and Internalization and Activating Apoptosis of Infected Cells

Abstract: Bovine viral diarrhea virus (BVDV) causes a severe threat to the cattle industry due to ineffective control measures. Gypenoside is the primary component of Gynostemma pentaphyllum, which has potential medicinal value and has been widely applied as a food additive and herbal supplement. However, little is known about the antiviral effects of gypenoside. The present study aimed to explore the antiviral activities of gypenoside against BVDV infection. The inhibitory activity of gypenoside against BVDV was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…Secondary metabolism not only endows plants with the ability to adapt to the ecological environment, but also provides abundant pharmaceutical ingredients of considerable health benefits to humans (Ramakrishna and Ravishankar, 2011;Thimmappa et al, 2014;Li et al, 2015). Terpenoid saponins and flavonoids are two important secondary metabolites, several of which have been proven to exhibit antiviral, antifungal, and anticancer properties (Zhang et al, 2018;Bonta, 2020;Russo et al, 2020;Yang et al, 2021). G. pentaphyllum is a traditional Chinese medicinal herb and known for its industrial use.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary metabolism not only endows plants with the ability to adapt to the ecological environment, but also provides abundant pharmaceutical ingredients of considerable health benefits to humans (Ramakrishna and Ravishankar, 2011;Thimmappa et al, 2014;Li et al, 2015). Terpenoid saponins and flavonoids are two important secondary metabolites, several of which have been proven to exhibit antiviral, antifungal, and anticancer properties (Zhang et al, 2018;Bonta, 2020;Russo et al, 2020;Yang et al, 2021). G. pentaphyllum is a traditional Chinese medicinal herb and known for its industrial use.…”
Section: Discussionmentioning
confidence: 99%
“…Later, the virions were resuspended in the culture medium. Cell lysates were harvested for Qrt-PCR and fixed cells were used for IFA analysis [28].…”
Section: Viral Attachment Internalization Replication Release and Ina...mentioning
confidence: 99%
“…Gypenosides are the principal components responsible for the diverse and significant effects of G. pentaphyllum. The pharmacological activities include anti-cancer [2], antiinflammatory [3], anti-viral [4], anti-atherogenic [5], antioxidant [6], anti-hyperglycemia [7] and neuroprotective activities [8]. Until now, more than 300 gypenosides have been isolated and structurally elucidated from G. pentaphyllum [9].…”
Section: Introductionmentioning
confidence: 99%
“…Gypenosides from G. pentaphyllum also possess antiviral effects [17]. Yang et al demonstrated that gypenoside inhibited bovine viral diarrhea virus replication by interfering with viral attachment and internalization and by activating apoptosis of infected cells [4]. Crude extracts of G. pentaphyllum were also proven to have antiviral activity against highly pathogenic H5N1 avian influenza virus [18].…”
Section: Introductionmentioning
confidence: 99%